A pooled analysis of the incidence and mortality risk of atrial fibrillation in patients with COVID-19 - Nan-Nan Shen; Jia-Liang Wang; Xin-Wen Liu; Yong-Ping Fu; Xue-Fang Chen (PeerJ)
Background There exist serious cardiovascular complications subsequent to SARS-Cov2 infection (COVID-19); however, the association between COVID-19 and atrial fibrillation (AF) remains to be elucidated. We aimed to assess the prevalence of AF among COVID-19 patients and its associated risk of death. Methods The present systematic review was performed in accordance with the PRISMA guidelines. The protocol was registered with CRD42022306523. A comprehensive literature search was performed across PubMed, Embase, and Cochrane databases to identify studies reporting on the prevalence of pre-existing or new-onset fibrillation (AF), and/or the associated clinical outcomes in patients with COVID-19 from January 2020 to December 2023. The random-effect model was used to estimate the prevalence of AF and its related mortality. Results A total of 80 studies, including 39,062,868 COVID-19 patients, were identified in the present investigation. The prevalence rates of pre-existing AF or new-onset AF were 10.5% (95% CI [9.3–11.7%]) or 10.3% (95% CI [6.2–14.5%]), respectively. Subgroup analysis revealed a two fold higher incidence of AF in older patients (≥65 years) compared to younger patients (<65 years) (14.4% vs. 6.4%). The highest rate of AF was observed in Europeans (10.7%, 95% CI [10.2–11.2%]), followed by Northern Americans (10.0%, 95% CI [8.2–11.7%]), while Asians demonstrated a lower prevalence (2.7%, 95% CI [2.2–3.3%]). Notably, severe COVID-19 patients displayed a significantly elevated prevalence of AF at 14.l% (95% CI [13.3–14.9%]), which was approximately 2.5-fold higher than that in non-severe patients (5.2%, 95% CI [4.8–5.5%]). Both pre-existing (HR: 1.83, 95% CI [1.49–2.17]) and new-onset AF (HR: 3.47, 95% CI [2.26–5.33]) were associated with an increased mortality risk among COVID-19 patients. Furthermore, the effect on mortality risk was more significant in Asians (HR: 5.33, 95% CI [1.62–9.04]), compared to Europeans (HR: 1.68, 95% CI [1.24–2.13]) and North Americans (HR: 2.01, 95% CI [1.18–2.83]). Conclusion This study comprehensively investigated the association between AF and COVID-19 in a real-world setting. Notably, a high prevalence of AF was observed among older individuals, severe COVID-19 patients, and in Europe and Northern America. Moreover, co-existing AF was found to be associated with an increased risk for mortality. Further investigations are warranted to improve the management and outcomes of COVID-19 patients with AF.